Ethnic Identity and Educational Outcomes - Teresa Randazzo; Matloob Piracha (Institute of Labor Economics (IZA), 2024)
We study the role of immigrant children's ethnic identity in their educational performance and preferences/aspirations in Italy. We find that students with a weak sense of Italian belonging show a low performance in reading and mathematics and higher probability of grade retention. Moreover, children in middle secondary school with a weak sense of Italian identity have a low preference towards academically-oriented high secondary track which normally increases the likelihood of pursuing a university degree. We also find that the intention of immigrant children in high secondary schools to enrol at university decreases if they have a weak Italian identity. We exploit gender heterogeneity finding that females are more adversely affected in their educational aspirations when they have not built a strong sense of Italian identity. Immigrant children will soon form a very important component of the Italian labour force and shedding light on their educational outcomes will help us understand their performance in the Italian labour market better.
Keywords: F22; J15; I2; Z13; 330; ethnic identity; educational performance; educational preferences